1991
DOI: 10.1002/jso.2930480531
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic resections for colorectal metastases: The italian multicenter experience

Abstract: In 1989 there were 151,000 new cases of colorectal carcinoma in the United States. Approximately 50% of these patients will be at risk of developing liver metastases together with other sites of recurrence. However, the liver will be the main site of relapse in only 14,000 patients with colorectal cancer. [1,2,12,15,19]. Approximately 25% of patients with colorectal carcinoma have technically resectable hepatic metastases at the time of operation for primary lesion, and an additional 8-25% will develop metachr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 35 publications
0
7
0
2
Order By: Relevance
“…The prognosis of synchronous liver metastasis has been reported by several investigators 5,[9][10]22,41,68,69,96,102,103,109,110,[123][124][125][126][127] as being worse than that of metachronous metastasis, while several others postulate that clinical stage 4,10,16,27,41,61,76,83,86,87,90,96,103,123,126,[128][129][130] or lymph node metastasis 8,23,38,40,41,80,86,89,90,96,118,[131][132][133][134][135]...…”
Section: Recurrence In the Liver Following Primary Hepatectomymentioning
confidence: 98%
“…The prognosis of synchronous liver metastasis has been reported by several investigators 5,[9][10]22,41,68,69,96,102,103,109,110,[123][124][125][126][127] as being worse than that of metachronous metastasis, while several others postulate that clinical stage 4,10,16,27,41,61,76,83,86,87,90,96,103,123,126,[128][129][130] or lymph node metastasis 8,23,38,40,41,80,86,89,90,96,118,[131][132][133][134][135]...…”
Section: Recurrence In the Liver Following Primary Hepatectomymentioning
confidence: 98%
“…It is arguable whether there is a significant difference in survival rate after hepatic resection between patients with solitary metastasis and those with multiple lesions (Table 1). However, a general consensus appears to have been reached that, in patients with four or more metastases, there is an association between the number of metastases and survival, although the results in individual reports vary: Iwatsuki et al11 reported that none of the seven patients with four or more lesions in their series of 60 patients with hepatic resections survived for more than 3 years, whereas Sheele et al,21 Doci et al,14 and Fegiz et al31 found no such a relationship. Figure 1a,b shows the results of our own experience with 65 patients who had hepatic resections for liver metastasis of colorectal cancer.…”
Section: Indications For Surgery and Outcome In Patients With Multimentioning
confidence: 99%
“…Insgesamt [24,25]. Nach internationalen Daten entwickeln mehr als 50% der Patienten mit einem Kolonkarzinom Lebermetastasen als alleinige Lokalisation oder mit anderen Metastasenlokalisationen [2,4,8]. Hier sind unsere Daten deutlich niedriger (29,2%); dies ist durch die durchschnittliche Nachbeobachtungszeit von 28,4 Monaten zu erklären.…”
Section: Diskussionunclassified
“…25% der Patienten, die an einem kolorektalen Karzinom erkranken, soll sich eine isolierte Lebermetastasierung mit der Möglichkeit einer Resektabilität entwickeln [2,8]. Andere Autoren sehen den Anteil von Patienten mit potenziell resektablen Metastasen allerdings geringer [14,19].…”
Section: Diskussionunclassified